2021
DOI: 10.1007/s43032-021-00729-6
|View full text |Cite
|
Sign up to set email alerts
|

Cryoprotective Effect of Pentoxifylline on Spermatogonial Stem Cell During Transplantation into Azoospermic Torsion Mouse Model

Abstract: BackgroundPreserving the spermatogonial stem cells (SSCs) in long periods of time during the treatment of male infertility using stem cell banking systems and transplantation is an important issue. Therefore, this study was conducted to develop an optimal cryopreservation protocol for SSCs using 10 mM pentoxifylline (PTX) as an antioxidant in basal freezing medium. MethodsTesticular torsion -a mouse model for long-term infertility-was used to transplant fresh SSCs (n=6), fresh SSCs treated with PTX (n=6), cryo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The high expression for these three markers (PLZF, Thy-1 and α-6 integrin) in SSCs indicated the primary phases of the evolvement of the spermatogenic lineage in isolated SSCs whose differentiation process had not yet initiated and confirmed that SSCs collected after digestion enzymatic were in the undifferentiated stage. The high expression of SSC identification markers in this study was consistent with other studies [ 35 37 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The high expression for these three markers (PLZF, Thy-1 and α-6 integrin) in SSCs indicated the primary phases of the evolvement of the spermatogenic lineage in isolated SSCs whose differentiation process had not yet initiated and confirmed that SSCs collected after digestion enzymatic were in the undifferentiated stage. The high expression of SSC identification markers in this study was consistent with other studies [ 35 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…Increased expression of Stra8 and SCP3 was considerable in the freeze + Mel group compared to the freeze group. Malekzadeh et al found that adding pentoxifylline to the freezing medium improved the recovery of post-thaw SSCs and increased the expression of proliferation (ID4 and Ddx4) and differentiation (SCP3 and C-Kit) proteins compared to frozen–thawed SSCs in the basic freezing medium after transplantation into azoospermic mice [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Schramm et al reported that the maximum PTX concentration in seminal plasma was only 75 ng/ml (0.3 μM) ( Schramm and Hinze, 1980 ). Recent two in vitro studies demonstrated the protective impact of PTX on spermatogenesis in mice models with both concentration levels higher than 0.3 μM ( Dhulqarnain et al, 2021 ; Malekzadeh et al, 2021 ). 3) Increased blood perfusion and reduced blood viscosity in testes and epididymis: Pozor and his colleagues confirmed that PTX-treated stallions had significantly higher total arterial blood flow rate than controls, delaying the seasonal decrease of testicular perfusion, without sperm quality and total sperm volume improved ( Pozor et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with results showing that cryopreservation of testicular tissue by slow-freezing in 5% DMSO does not seem to affect the long-term culture of human testicular cells with regard to the presence of germ cell and somatic cell populations ( 32 ). Further optimization and possible addition of novel cryoprotectants, such as the antioxidant pentoxifylline ( 33 ) to the freezing medium may further improve the preservation of human SSC viability. Our research group cryopreserved testicular tissues obtained from orchiectomies of two adult patients with prostate cancer using various protocols in a pilot study.…”
Section: Cryopreservationmentioning
confidence: 99%